The Effect of Optimism Training Through Educational Movies on the Students' Social Competence - Alireza Jafari Baghkheirati; leila ghahramani; Sareh keshavarzi; Mohammad Hossein Kaveh (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Optimism is defined as the tendency to choose the most hopeful view and an emotional and cognitive preparation regarding the superiority of good things over bad ones in life. Social competence is one of the main constructs of mental health and is defined as an individual's ability to act adaptively relative to one's age and cognitive ability. Development of social competence has been considered as one of the best predictors of behavior, academic achievement, and social, emotional, and behavioral problems both in present and future. The present study aimed to determine the effect of optimism training via educational movies on the students' social competence. Methods: This quasi-experimental study aimed to determine the effectiveness of optimism educational movie on the social competence of male high-school students in Shiraz. In this study, 240 samples were divided into an intervention and a control group. The educational content was presented through group discussion and question and answer in two sessions. The data were collected using Flener's social competence questionnaire and were analyzed by the SPSS19 statistical software. Results: There was a significant increase in all social competence factors, including behavioral skills (189.35±31.09), motivation and expectations (33.06±8.94), cognitive skills (15.65±3.83), and emotional skills (16.58±3.78), in the intervention group compared to the control group after the training (p<0.001). Conclusion: The results showed the effectiveness of optimism educational movie on social competence factors. Considering the high-school students' problems, optimism training via social competence factors can affect different aspects of their lives and strengthen their interpersonal and social relationships.